A HaemSTAR is born; a trainee-led, UK-wide research network in haematology. Issue 6 (2019) - Nicolson, Phillip LR; Desborough, Michael JR; Hart, Daniel; Biss, Tina T; Lowe, Gillian C; Toh, Cheng-Hock
No abstract available